The Effect of Regional Minimum Wage and Inflation on HDI in Central Java - Siska Ardi Cahyanti; Sotya Fevriera (Jurnal Ekonomi Pembangunan, 2020)
Since 2017 Central Java has a high Human Development Index (HDI); its rank in 2019 is still the same as in 2010. The study investigates regional minimum wage and inflation facts in Central Java and how the HDI estimation model's constants differ differregency/city in different regions of Central Java. The study utilizes the Fixed Effect Model built using panel data for 2010-2019. It employs the Least Square Dummy Variable Model to get the difference constant for each regency and city in Central Java. The FEM model implies that the effects of RMW and inflation are the same for all regencies/cities, caused by the same cultural background. The results of this study show that RMW and inflation have significant positive effects on HDI and that cities tend to have higher constants compared to regencies